STUDENT LEARNING ACHIEVEMENT MODEL: LEARNING MOTIVATION AND LEARNING INTEREST WITH PARENTS' ATTENTION AS INTERVENING VARIABLES - Hanna Pratiwi; Desi Permata Sari; Ai Elis Karlinda; Selvi Yona Sari; Olandari Mulyadi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The aim of this study was to examine the extent to which the influence learning motivation and interest in learning have on student achievement with parental attention as an intervening variable. Method collection data through survey and spread questionnaire, with a sample of 100 respondents obtained by the saturated sample formula at The population of the UPI YPTK campus is 100. The analytical method used is the inner model and path coefficients. Results study which obtained based on path coefficients obtained: 1) None influence positive which significant motivation to learn to student learning achievement significant value 0.994 <0.05. 2)There are influence positive which significant interest to learn to performance student study where significant value 0.000>0.05. 3) None influence positive which significant motivation to learn to parents attention where significant value 0.063 <0.05. 4) There are influence positive which significant interest in learning to parents attention. where score significant 0.000<0.05. 5) No there is influence positive which significant parents attention to student learning achievement. where significant value 0.422>0.05. The author provides suggestions Expected to parents give input and suggestion to children to increase interest in learning so that they can enhancement performance study and etc, so that parent able to improve facilities and a safe environment for children to learn To use can maintain even improve performance study